Leadership, Entrepreneurial Characteristics, and MSME Performance: The Mediating Role of Interpersonal Communication - Nandang Nandang; Asep Jamaludin; Wanta Wanta; Rengga Madya Pranata (International Journal of Information System and Innovation Management (IJISIM), 2025)
This study aims to examine the effects of leadership and entrepreneurial characteristics on business performance, with interpersonal communication serving as a mediating variable among Micro, Small, and Medium Enterprises (MSMEs) in Telukjambe Timur District, Karawang Regency. The study population comprised 147 MSME actors, from which a sample of 105 respondents was selected. A descriptive quantitative approach was employed, and Structural Equation Modeling (SEM) was used to analyze the relationships among the variables in the proposed research model. The findings reveal that leadership and entrepreneurial characteristics have positive and significant effects on interpersonal communication. Furthermore, both leadership and entrepreneurial characteristics positively influence business performance. Interpersonal communication also demonstrates a positive effect on business performance and plays a significant mediating role in the relationship between leadership, entrepreneurial characteristics, and business performance. These results highlight the importance of effective leadership, strong entrepreneurial traits, and interpersonal communication in enhancing MSME performance.